Effectiveness of Brandt Daroff and Water-Based Exercise In Patients with Vertigo: Case Report - Yulianti, Dwi; Pristianto, Arif; Santoso, Totok Budi (Faculty of Medicine, Universitas Jember, 2025)
The displacement of otoliths into the semicircular canals causes the most common type of peripheral vertigo, known as Benign Paroxysmal Positional Vertigo (BPPV). This condition can disrupt balance and increase the risk of falls, especially when the head position changes suddenly. The purpose of this case report is to determine how effective the combination of Brandt-Daroff exercises and hydrotherapy is in improving balance in BPPV patients. A 69-year-old woman with vertigo underwent the Dix-Hallpike maneuver and an intervention consisting of Brandt-Daroff exercises and hydrotherapy twice weekly under supervision for six weeks. Balance evaluation was conducted before and after therapy using the M-CTSIB (for static balance) and TUG-T (for dynamic balance). Following the intervention, the TUG-T score decreased from 21.5 to 18, indicating improved mobility and patient response. The M-CTSIB score also increased significantly, particularly for eyes closed and unstable surfaces, from 15 to 22. Conditions without visual support also improved, indicating good vestibular adaptation. Patients reported no longer experiencing vertigo when changing positions and being able to engage in activities without fear of falling. These results suggest that Brandt-Daroff exercises and hydrotherapy can serve as non-pharmacological methods to improve balance and quality of life for patients with BPPV.